Using stable isotopes in hummingbird breath to estimate reliance on supplemental feeders. Issue 2 (7th February 2023) - Wolf, Nathan; Smeltz, T. Scott; Cook, Craig; Martinez del Rio, Carlos
Abstract: Understanding the ecological consequences of supplemental feeding to both hummingbirds and the plants they pollinate is complicated by logistical challenges associated with assessing relative dietary resource use with commonly applied observational methods. Here, we describe the results of research conducted to assess the relative use of feeder and flower nectar by Broad‐tailed ( Selasphorus platycercus ) and Rufous hummingbirds ( Selasphorus rufus ) using two distinct methodological variations to measure the δ 13 C values of exhaled CO2 . Because of the relatively quick time in which both species switch from exogenous to endogenous resources to fuel metabolism, our experiment allowed us to assess resource use at two timescales. Our results suggest variability in the relative contributions of the two dietary sources within and among species and timescales, with most birds employing a mixture of feeder and flower sugars as fuel sources. This diversity in relative resource use may mitigate potential negative effects of supplemental feeding on hummingbirds and their plant symbionts. Abstract : Posterior distributions for the isotopic composition of exhaled CO2 in fed birds (δ 13 C0 ; first column), the isotopic composition of exhaled CO2 in fasted birds (δ 13 C∞ ; second column), and associated overlap for Broad‐tailed and Rufous hummingbirds. Y axis values represent frequencies from 10, 000 Markov chain Monte Carlo samples, with higher frequencies representing greater numbers of individuals likely to employ a particular dietary resource or mixture. Vertical dotted lines and vertical dashed lines represent the 85% highest posterior density intervals for δ 13 C0 and δ 13 C∞, respectively.